PENGARUH RISIKO AUDIT, TEKNIK-TEKNIK AUDIT INVESTIGATIF TERHADAP PENDETEKSIAN KECURANGAN DAN PROFESIONALISME AUDITOR - Sandari, Tries Ellia (JEA17: Jurnal Ekonomi Akuntansi, 2019)
ABSTRACTThe purpose of this study was to determine the effect of Risk Audit, Audit Investigation  Techniques on Fraud Detection and Professionalism Auditor (studies on public accounting firm in East Java). Public accounting profession is responsible for raising the level of reliability of the financial statements. This research uses quantitative descriptive. The population in this study is 20 KAP in East Java and is active from 2015-2017. Data collection techniques using purposive sampling The sample used in this study are structural Equation Modelling (SEM) using the help pf Partial Least Sqaure (PLS) software. And hypothesis in this study indicate that five hypotheses were accepted. The significance of this hypothesis shows directly through audit risk, audit investigation techniques, fraud detection and professionalism auditor. Keyword : Risk Audit, Audit Investigation Techniques, Fraud                    Detection,  Professionalism Auditor.